Preparation and Characterization of Polybutylene Succinate Reinforced with Pure Cellulose Nanofibril and Lignocellulose Nanofibril Using Two-Step Process - Azelia Wulan Cindradewi (MDPI AG, 2021)
This study reports the preparation of a polybutylene succinate (PBS) film reinforced with pure cellulose nanofibril (PCNF) and lignocellulose nanofibril (LCNF) by a two-step process that consists of solvent dispersion and twin-screw extrusion. Compared to the conventional one-step process, this method offered improved mechanical properties. The addition of 5% CNF increased the tensile properties up to 18.8%. Further, the effect of the lignin content was also studied by using LCNF as a reinforcement. The LCNF was prepared with and without a deep eutectic solvent (DES) pretreatment to gain LCNF with a lignin content that varied between 5, 19, and 30%. The mechanical properties results show that a 5% addition of LCNF to the PBS matrix increased its tensile strength and elastic modulus. Further, the morphological and thermal properties of the composites were also studied in detail.